2014
DOI: 10.1007/s10880-014-9396-1
|View full text |Cite
|
Sign up to set email alerts
|

Parent routines for managing cystic fibrosis in children

Abstract: Management of cystic fibrosis (CF) is burdensome and adherence is often suboptimal. Family routines are associated with adherence and health outcomes in other disease populations. Few studies have examined routines in CF. The study's aim was to describe parent experiences developing and utilizing CF care routines. Semi-structured interviews with a convenience sample of 25 parents of children under 13 years of age with CF were analyzed using phenomenological analysis. Three domains emerged: parent experiences d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
0
13
0
2
Order By: Relevance
“…26 A study in children with cystic fibrosis reported parental barriers to treatment regimens such as being overwhelmed by the burden of daily care and their lack of experience with caring for a child with a debilitating and chronic illness. 27 Therefore, the identified levels of confidence and perceived effectiveness in parents performing an MAC on children with NMD may potentially be assisting compliance to treatment regimens. Although the impact of exploring perceptions on therapy adherence and treatment outcomes could not be explained within the scope of this study, further research may provide clarification.…”
Section: Discussionmentioning
confidence: 99%
“…26 A study in children with cystic fibrosis reported parental barriers to treatment regimens such as being overwhelmed by the burden of daily care and their lack of experience with caring for a child with a debilitating and chronic illness. 27 Therefore, the identified levels of confidence and perceived effectiveness in parents performing an MAC on children with NMD may potentially be assisting compliance to treatment regimens. Although the impact of exploring perceptions on therapy adherence and treatment outcomes could not be explained within the scope of this study, further research may provide clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Proactive assessment and intervention can help promote family wellness, resilience, and coping, and minimize future risks that impede achieving health targets. During the infant and preschool period, it is important to focus on parental mental health, the development of healthy attachments and positive parenting skills to build consistent, daily CF care routines 10 …”
Section: Introductionmentioning
confidence: 99%
“…They require special care skills and competencies from their family caregivers for their rehabilitation, requiring training, supervision and observation of care. It is clear that relatives, when interacting with the nursing staff, seeks to share feelings and perceptions regarding the finitude and fragility of the human condition, which a chronic and severely severe disease imposes (6) . It is considered an interactive sharing when the human being not only reacts to the actions of the other, but understands the context in which he finds himself, which can positively influence healthy ways of living (7) .…”
Section: Introductionmentioning
confidence: 99%